Effect of River Shell Particles on The Thermal Conductivity and Flexural Strength of The Polyester Resin - S. Mahjoob, Dawood; N. Mustafa, Samir; M. Mahan, Hamid (International Journal of Engineering and Technology, 2018)
In the present research, the effect of micro river shell percentage on thermal conductivity properties and flexural strength of the polyester compound with different Weight amount (5%, 10%, 15%, 20%, 25%) to the resin. Glacial river shell particle size was introduced in 8 Î¼m, therefore, The thermal conductivity test and flexural strength were performed on samples. The results indicated river shell percentage decrease the thermal conductivity of a polyester composite with an ideal percentage was 10% and the highest flexural strength weight amount 5wt% of River shell.Â